2016
DOI: 10.1080/14767058.2016.1237498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outcomes associated with trial of labor after cesarean delivery after a change in clinical practice guidelines in an academic hospital

Abstract: Adoption of ACOG's TOLAC practice changes can increase VBAC rates without increasing maternal-neonatal morbidity from TOLAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…We found a positive correlation between Bishop's score and success of TOLAC, consistent with Francis (2005) who demonstrated a relationship between risk of cesarean delivery and unfavorable Bishop score at admission [25]. Similarly, several related studies have confirmed that the Bishop's score, at delivery, affects the success rate of TOLAC [17,26]. In the present study, the OR of Bishop's score was higher, with a relatively narrower confidence interval than that reported in previous studies (OR, 3.27; 95% CI, 2.49 to 4.55).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found a positive correlation between Bishop's score and success of TOLAC, consistent with Francis (2005) who demonstrated a relationship between risk of cesarean delivery and unfavorable Bishop score at admission [25]. Similarly, several related studies have confirmed that the Bishop's score, at delivery, affects the success rate of TOLAC [17,26]. In the present study, the OR of Bishop's score was higher, with a relatively narrower confidence interval than that reported in previous studies (OR, 3.27; 95% CI, 2.49 to 4.55).…”
Section: Discussionsupporting
confidence: 90%
“…Particularly, we used external verification of the widely used Grobman's model, to add corresponding features before delivery, and achieved superior predictive ability. Based on a clear trend of benefits from the successful vaginal delivery among those trials of labor after cesarean section, it is evident that VBAC failure exacerbates many risks, including bleeding, increased blood transfusions, uterine rupture and endometritis, as well as infant asphyxia or perinatal death [8,17,18]. Consequently, obstetricians prefer a more conservative approach during TOLAC to avoid medical disputes owing to the complex physician-patient relationship as well as the associated high work-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…Again, in our study, peripartum hysterectomy, bowel, and bladder injury among major complications were observed in none of the patients. In a recent study performed [18]. This difference was found to be significant (p = 0.03).…”
Section: Discussionmentioning
confidence: 84%
“…The trial of labor after cesarean (TOLAC) is an attempt to reduce CS rates. Several national medical associations have provided practice guidelines for vaginal birth after cesarean section (VBAC) [4, 5], but these differ across countries [6]. Generally speaking, VBAC is relatively safe when compared with repeat CS [7] .However, TOLAC rates have dropped significantly worldwide in recent years [8, 9].…”
Section: Introductionmentioning
confidence: 99%